Semi-Empirical Models for the Bidirectional Water-Leaving Radiance: An Analysis of a Turbid Inland Lake - Han, Zeying; Gu, Xingfa; Zuo, Xin; Bi, Kaiyi; Shi, Shuaiyi (Frontiers in Environmental Science, 2022)
When a precise quantitative analysis of satellite measurements over bodies of water is required, the bidirectional effects of water-leaving radiance must be considered. The bidirectional reflectance distribution function (BRDF) is used to estimate the directional dependency of the radiance. Previous research on BRDF has focused on oceanic waters; few studies on turbid inland waters have been done. In this paper, using multi-angle MISR measurements, five semi-empirical BRDF models (MAG2002, Lee2004, Park-Ruddick2005, Woerd-Pasterkamp2008 and Lee2011) were quantitatively compared and an adaptive algorithm was proposed over a typical turbid inland lake, Taihu Lake, China. Our results reveal the following: (1) the Woerd-Pasterkamp2008 and Lee2011 models provide the best fits with correlation coefficients greater than 0.8; (2) when prior modeling parameters were used, the Lee2011 model was still the most accurate with RMSEs less than 1.1%, while the accuracy of the Woerd-Pasterkamp2008 model varied; and (3) the use of an adaptive algorithm including an empirical rule based on the ratio of bb/a improved the accuracy. The results provide a theoretical basis for BRDF models and BRDF effects over inland Case II waters. They also provide a priori knowledge for future studies on water constituents and the quantitative inversion of atmospheric parameters.